Deciphering the virulence of Mycobacterium avium subsp. paratuberculosis isolates in animal macrophages using mathematical models. (7th May 2019) - Alonso-Hearn, Marta; Magombedze, Gesham; Abendaño, Naiara; Landin, Mariana; Juste, Ramon A.
Highlights: Using mathematical models different susceptibilities of animal macrophages to Map infection were confirmed. Our study confirmed distinct virulence profiles for Map isolates. Our models allow us to differentiate between potential progressive and non-progressive Map infections. Abstract: Understanding why pathogenic Mycobacterium avium subsp. paratuberculosis (Map) isolates cause disparate disease outcomes with differing magnitudes of severity is important in designing and implementing new control strategies. We applied a suite of mathematical models: i) general linear, ii) and neurofuzzy logic, to explain how the host of origin of several Map isolates, Map genotype, host, macrophage-based in vitro model and time post-infection contributed to the infection. A logistic growth ordinary differential equation (ODE) model was applied to estimate within macrophage growth rates for the different Map isolates. The models revealed different susceptibilities of bovine and ovine macrophages to Map infection and confirmed distinct virulence profiles for the isolates, judged by their ability to grow within macrophages. Ovine macrophages were able to internalize Map isolates more efficiently than bovine macrophages. While bovine macrophages were able to internalize Map isolates from cattle with more efficiency, ovine macrophages were more efficient in internalizing ovine isolates. Overall, Map isolates from goat and sheep grew minimally within macrophages or did not grow but were able to persist by maintaining its initial population. In contrast, the ability of the bovine isolates and the non-domesticated animal isolates to grow to higher CFU numbers within macrophages suggests that these isolates are more virulent than the sheep and goat isolates, or that these isolates are better adapted to infect domestic ruminants. Overall, our study confirms the different virulence levels for the Map isolates and susceptibility profiles of host macrophages, which is crucial in increasing our understanding of Map infection.